2021
DOI: 10.3389/fgene.2021.763995
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of S, M and N Structural Proteins by the Protein–RNA Recognition Code Leads to Genes/proteins that Are Relevant to the SARS-CoV-2 Life Cycle and Pathogenesis

Abstract: In this conceptual review, based on the protein–RNA recognition code, some theoretical sequences were detected in the spike (S), membrane (M) and capsid (N) proteins that may post-transcriptionally regulate the host genes/proteins in immune homeostasis, pulmonary epithelial tissue homeostasis, and lipid homeostasis. According to the review of literature, the spectrum of identified genes/proteins shows that the virus promotes IL1α/β–IL1R1 signaling (type 1 immunity) and immunity defense against helminths and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 146 publications
0
4
0
Order By: Relevance
“…Decreased plasma product from XYLB was hypothesized as one of the potential metabolomics biomarkers of COVID-19. [34][35][36] CLDN6 (Claudin-6) has a large role in tight junction-specific obliteration of the intercellular space (which has a role in microbial infection), and also functions as a receptor for hepatitis C virus entry into hepatic cells. UBTF gene is associated with neurodegeneration, brain atrophy, intellectual disability, retinoblastoma, pediatric acute myeloblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased plasma product from XYLB was hypothesized as one of the potential metabolomics biomarkers of COVID-19. [34][35][36] CLDN6 (Claudin-6) has a large role in tight junction-specific obliteration of the intercellular space (which has a role in microbial infection), and also functions as a receptor for hepatitis C virus entry into hepatic cells. UBTF gene is associated with neurodegeneration, brain atrophy, intellectual disability, retinoblastoma, pediatric acute myeloblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PLA2 contributes to anti-helminth defense by hydrolyzing membrane phospholipids (Th2-defence, production of IL4 and IL5 cytokines, allergy/asthma) [181]. Previous "1-L transcription" revealed that SARS-CoV-2 reorients the immune response to type 2 immunity [10]. On the other hand, PLA2 products represent the first step in the cyclooxygenase (COX) pathway.…”
Section: Immune Responses and Inflammationmentioning
confidence: 99%
“…This bioinformatics study focuses on possible post-transcriptional regulation of the SARS-CoV-2 spike protein S1 subunit in host cells/tissues. Ten regulated genes were previously identified by 1-L transcription [10] in relation to protein-RNA post-transcriptional regulation of the S1 subunit: PARG (poly[ADP-ribose] glycohydrolase), DAW1 (dynein assembly factor with WD repeats 1), ZYG11B (zyg-11 family member B, cell cycle regulator), PIKFYVE (phosphoinositide kinase, FYVE-type zinc finger containing), RABEP1 (rabaptin, RAB GTPase binding effector protein 1), MSRA (methionine sulfoxide reductase A), PLB1 (phospholipase B1), TJP2 (tight-junction protein 2), ZEB2 (zinc finger E-box binding homeobox 2), and XYLB (xylulokinase B). As confirmed experimentally by others, these genes/proteins are important during SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…1-L transcription is a simple computational method successfully tested on the life cycle and pathogenesis of SARS-CoV-2 [ 11 , 12 ]. In this method, the amino acid sequence of the RNA binding protein (RBP) was transcribed with a 1-L protein-RNA recognition code into compatible RNA sequences, which were then used for classical BLASTn screening in the human transcriptome to identify genes that can be post-transcriptionally regulated by the analyzed RBP.…”
Section: Introductionmentioning
confidence: 99%